DNA–LIGAND COMPLEXES MELTING: THE EFFECT OF MULTIPLE BINDING MECHANISMS - Grigoryan, Z.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
Helix–coil transition of complexes DNA with two ligands of different binding mechanisms to native and melted regions of biopolymer is considered using the most probable distribution method. It was shown that obtained biphasic behavior of helix–coil transition curves depends on both binding affinity and concentration of ligands in solution. Thermodynamic behavior of the ligands having higher and lower affinity to the native DNA is compared.
Keywords: helix–coil transition; biphasic denaturation; multiple binding